BUENOS AIRES AND MONTEVIDEO: PARALLELISM AND DISPLACEMENT IN HISTORIC CENTERS (Andamios, Revista de Investigación Social, 2009)
The two capitals have a historical interaction that joins processes, destinies and societies, which is manifested in the physical, social and architectonic configuration of both cities. However, the ways in which these processes are dealt with and developed regarding built patrimony and its protection, intervention in the historic centers or the outline of public policies to foster their recovery do not show parallelisms, but rather marked displacements. This paper aims to expose them, focusing on aspects related to urban history and intervention, patrimony, and housing in the historic centers of Buenos Aires and Montevideo.
Keywords: Historic center; urban history; patrimony; intervention; housing